Genotype‐specific SNP map based on whole chromosome 3B sequence information from wheat cultivars Arina and Forno. Issue 1 (10th October 2012) - Shatalina, Margarita; Wicker, Thomas; Buchmann, Jan P.; Oberhaensli, Simone; Šimková, Hana; Doležel, Jaroslav; Keller, Beat
Summary Agronomically important traits are frequently controlled by rare, genotype‐specific alleles. Such genes can only be mapped in a population derived from the donor genotype. This requires the development of a specific genetic map, which is difficult in wheat because of the low level of polymorphism among elite cultivars. The absence of sufficient polymorphism, the complexity of the hexaploid wheat genome as well as the lack of complete sequence information make the construction of genetic maps with a high density of reproducible and polymorphic markers challenging. We developed a genotype‐specific genetic map of chromosome 3B from winter wheat cultivars Arina and Forno. Chromosome 3B was isolated from the two cultivars and then sequenced to 10‐fold coverage. This resulted in a single‐nucleotide polymorphisms (SNP) database of the complete chromosome. Based on proposed synteny with the Brachypodium model genome and gene annotation, sequences close to coding regions were used for the development of 70 SNP‐based markers. They were mapped on a Arina × Forno Recombinant Inbred Lines population and found to be spread over the complete chromosome 3B. While overall synteny was well maintained, numerous exceptions and inversions of syntenic gene order were identified. Additionally, we found that the majority of recombination events occurred in distal parts of chromosome 3B, particularly in hot‐spot regions. Compared with the earlier map based on SSR and RFLP markers, the number of markers increased fourfold. The approach presented here allows fast development of genotype‐specific polymorphic markers that can be used for mapping and marker‐assisted selection.